Dakwah Sosial sebagai Instrumen Soft Diplomacy: Studi Kasus Transformasi Anak Pekerja Migran Indonesia di Malaysia - Asmar, Afidatul; Suharto; Yuanita, Lira; Fachrul Saladin, Muhammad (Kementerian Luar Negeri Republik Indonesia, 2025)
The phenomenon of Indonesian migrant workers’ children (APM) in Malaysia affects not only their education and well-being but also the formation of cultural identity and national character. This study aims to analyze the role of social da’wah as an instrument of Indonesia’s soft diplomacy in Malaysia, focusing on moral–spiritual development, cultural preservation, and the strengthening of national identity among APM. A qualitative case study approach was employed to explore social da’wah activities within Indonesian diaspora communities, involving in-depth interviews, observations, and document analysis of programs conducted by religious instructors, da’wah institutions, and community groups. The findings indicate that social da’wah effectively shapes positive character, preserves Indonesian cultural values, and fosters a positive image of Indonesia in Malaysian society. Integrated social da’wah strategies aligned with soft diplomacy efforts have proven to strengthen bilateral relations between Indonesia and Malaysia while also enhancing Indonesia’s position through cultural diplomacy. The study recommends strengthening collaboration between the government, Indonesian embassies/consulates (KBRI/KJRI), da’wah institutions, and community organizations to expand program outreach, improve the quality of da’wah content, and maximize the use of digital media as an effective tool for cultural diplomacy.